Determinan Penerimaan Penggunaan Mobile Payment Qris (Quick Response Indonesian Standard) untuk Berinfaq di Masjid Raya Baiturrahman Semarang - Munif, Ahmat Saeful; Darwanto, Darwanto (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2023)
Infaq is the giving of some of the assets owned to others in expectation of the pleasure of Allah SWT. This study aims to determine the determinants of attitudes and intentions to use QRIS mobile payment for infaq among millennials and generation Z at the Baiturrahman Grand Mosque in Semarang. This study uses a quantitative method using primary data obtained by online questionnaires through Google Form. The sampling method used was non-probability sampling with purposive sampling technique. This study took a sample of 210 respondents from the mosque congregation using the Meta-UTAUT model, and the data analysis technique used was Partial least square (PLS) using WarpPLS 7.0 software. The results showed that performance expectations, social influence, facility conditions, and trust have a positive and significant effect on attitudes towards using QRIS mobile payments in infaq payments. In addition, facility conditions and trust have a positive and significant effect on the intention to adopt mobile payment technology, attitude towards use has a positive and significant effect on the intention to implement mobile payment technology. The Islamic religiosity variable also moderates the relationship between the influence of attitudes on behavioral intentions to use QRIS mobile payment for infaq.